Effects of cognitive training program on brain connectivity in older adults with subjective cognitive complaints and mild cognitive impairment: Prevention (nonpharmacological) / Cognitive interventions. (7th December 2020) - Soto, Marcio; Vilca, Brenda Nadia Chino; Camlla, Rosangela; Dengri, Lucia; Fernández, Ricardo Bruña; Maestú, Fernando; Parra, Mario A
Abstract: Background: Cognitive intervention programs have achieved improvements at the behavioral level at different stages of dementia, especially in the preclinical phases, what is not yet clear is the neurophysiological correlate of these improvements, especially at the level of resting brain connectivity. Our objective was to analyze the changes at the neurophysiological level after the application of a cognitive training program in pre‐clinical phases of dementia using high density electroencephalography (hdEEG). Method: An intrasubject design was applied. All subjects underwent clinical and cognitive measurements and resting state records in a hdEEG at baseline and 3 months later when the cognitive training sessions ended. The final sample was composed of 7 older adults with subjective cognitive complaints (mean age = 62.08, SD = 6.48) and 8 with mild cognitive impairment (mean age = 62.93, SD = 6.75); whom were evaluated with a large neuropsychological battery which include the domains of executive function and memory. Electrophysiological signals were recorded with a high density EEG (160 channels). The cognitive training program lasted 24 sessions distributed in 8 sessions for each cognitive domain (attention, executive function and memory). Result: The results show a significant improvement of the cognitive domains trained and a greater clustering and a more efficient processing of the default brain network. These changes seem to be associated with greater efficiency in information processing and a reduction in random physiological activation in preclinical stages of dementia Conclusion: These programs show clear evidence of changes at the brain level due to cognitive intervention, it is recommended to do follow‐up studies to assess their stability over time.